Genetic determination of migration strategies in large soaring birds: evidence from hybrid eagles. Issue 1884 (15th August 2018) - Väli, Ülo; Mirski, Paweł; Sellis, Urmas; Dagys, Mindaugas; Maciorowski, Grzegorz
Abstract : The relative contributions of genetic and social factors in shaping the living world are a crucial question in ecology. The annual migration of birds to their wintering grounds and back provides significant knowledge in this field of research. Migratory movements are predominantly genetically determined in passerine birds, while in large soaring birds, it is presumed that social (cultural) factors play the largest role. In this study, we show that genetic factors in soaring birds are more important than previously assumed. We used global positioning system (GPS)-telemetry to compare the autumn journeys and wintering ranges of two closely related large raptorial bird species, the greater spotted eagle Clanga clanga and the lesser spotted eagle Clanga pomarina, and hybrids between them. The timing of migration in hybrids was similar to that of one parental species, but the wintering distributions and home range sizes were similar to those of the other. Tracking data were supported by habitat suitability modelling, based on GPS fixes and ring recoveries. These results suggest a strong genetic influence on migration strategy via a trait-dependent dominance effect, although we cannot rule out the contribution of social interactions.